Effects of the second hydration shell on excited-state multiple proton transfer: Dynamics simulations of 7-azaindole: (h2o)1-5 clusters in the gas phase - Nawee Kungwan (2018)
Dynamics of the multiple excited-state proton transfer (ESPT) in clusters of 7-azaindole with up to five water molecules was investigated with quantum chemical methods. The ultrafast excited-state dynamics triggered by photoexcitation was simulated with the algebraic diagrammatic construction to the second-order scheme. Multiple ESPT through a hydrogen-bonded network is observed in the 100-fs scale. The probability of tautomerization is anti-correlated with the maximum free energy barrier in the excited state. An increasing number of water molecules tends to reduce the barrier by strengthening the hydrogen-bonded network. Barrierless reactions are found already for clusters with four waters. In structures presenting double hydrogen bond circuits, proton transfer happens mostly through the internal circuit by triple proton transfer. The overall role of the second hydration shell is of stabilizing the network, facilitating the proton transfer in the internal circuit. Proton transfers involving the second hydration shell were observed, but with small probability of occurrence. The proton-transfer processes tend to be synchronous, with two of them occurring within 10-15 fs apart. © Springer-Verlag Berlin Heidelberg 2014.